Genetic subclone architecture of tumor clone-initiating cells in colorectal cancer - Gießler, Klara Monika; Kleinheinz, Kortine; Hübschmann, Daniel; Balasubramanian, Gnana Prakash; Dubash, Taronish Dorab; Dieter, Sebastian M.; Siegl, Christine; Herbst, Friederike; Weber, Sarah; Hoffmann, Christopher M.; Fronza, Raffaele; Buchhalter, Ivo; et al. (Journal of experimental medicine, 2017)
A hierarchically organized cell compartment drives colorectal cancer (CRC) progression. Genetic barcoding allows monitoring of the clonal output of tumorigenic cells without prospective isolation. In this study, we asked whether tumor clone-initiating cells (TcICs) were genetically heterogeneous and whether differences in self-renewal and activation reflected differential kinetics among individual subclones or functional hierarchies within subclones. Monitoring genomic subclone kinetics in three patient tumors and corresponding serial xenografts and spheroids by high-coverage whole-genome sequencing, clustering of genetic aberrations, subclone combinatorics, and mutational signature analysis revealed at least two to four genetic subclones per sample. Long-term growth in serial xenografts and spheroids was driven by multiple genomic subclones with profoundly differing growth dynamics and hence different quantitative contributions over time. Strikingly, genetic barcoding demonstrated stable functional heterogeneity of CRC TcICs during serial xenografting despite near-complete changes in genomic subclone contribution. This demonstrates that functional heterogeneity is, at least frequently, present within genomic subclones and independent of mutational subclone differences.